The modern view on the concept of treatment of active stages of retinopathy of prematurity - A. V. Tereshchenko; Yu. A. Belyy; I. G. Trifanenkova; M. S. Tereshchenkova (Oftalʹmologiâ)
Purpose: To show the basic regulations of the complex retinopathy of prematurity (ROP) treatment with use of retinal pattern scanning laser coagulation and early vitrectomy.Methods: Pascal pattern scanning lasercoagulation is performed for stage 2 ROP type 2, stage 3 ROP type 2 and subclinical stageand early clinical stage of aggressive posterior ROP (S. N. Fyodorov Federal State Institution «IRTC «Eye Microsurgery» Kaluga Branchclassification). Early 3‑ports 25G vitrectomy is performed if ROP progressing 2‑4 weeks after the laser treatment.Results: In 2003‑2011 823 different interventions for infants with active ROP was performed: 737 retinal lasercoagulations, 3‑ports vitrectomy — 72, 3‑ports lensvitrectomy — 14. Treatment efficacy was 98.6 % for stage 2 and stage 3 ROP (regress of the disease occurred in 557 of 565 eyes), and 74.4 % for aggressive posterior ROP (regress of the disease occurred in 128 of 172 eyes). The total efficacy of the complex treatment was 92.9 % (regress of the disease occurred in 685 of 737 eyes).Conclusion: The basic regulations of the complex ROP treatment are early, within first 6 weeks of chronologic age, photocoagulationto delay progression of the retinal detachment and to stabilize vascularity, and early vitrectomy if ROP progressing after the lasertreatment.